СОВРЕМЕННЫЕ ИНФОРМАЦИОННЫЕ ТЕХНОЛОГИИ В СИСТЕМЕ УПРАВЛЕНИЯ (International Journal of Innovative Technologies in Economy, 2018)
Level of informatization of administrative processes became one of the most important indices of the social and economic progress made by the state and the separate organization. From the qualitative side increase in information volumes used in the decision of tasks of control of the organizations leads to rationalization of human work and growth of welfare. Under the influence of the described processes already now in human society the group of people for whom operation with information became the major professional work was created.